Risk perception and cultural differences of Latinos across the residential, commercial, and heavy civil construction sectors - Bormann, Kane, author; Lopez del Puerto, Carla, advisor; Gilkey, Dave, committee member; Clevenger, Caroline, committee member (Colorado State University. Libraries, 2012)
In the field of construction, Latino workers currently suffer a disproportionate higher rate of injuries and fatalities than non-Latino workers. Socio cultural barriers exist that may contribute to this disproportionately higher rate; but, what effect does the sector of the construction industry employing the Latino worker have on safety incidents? The purpose of this study is to investigate differences in Latino construction worker's perceptions about safety culture and risk across the three construction sectors of residential, commercial, and heavy civil. This study is a continuation of the research collected for a cross-sectional study on Safety Culture and Risk Perception differences between Latino and non-Latino Construction workers. Analysis was conducted on 219 Latino responses to surveys collected in the Denver Metro and Northern Colorado areas. This study found that significant difference was exhibited between Latinos in different sectors of construction on six different questions. Those questions were, work productivity and quality having a higher priority than safety, feeling uncomfortable with work practices being observed and recorded, some safety rules and procedures being difficult to understand, immigrant workers making the worksite unsafe, willing to take more risks than coworkers, and the dangers present on construction sites cannot cause my death or the death of others. The research and results from this study will add to the literature of available knowledge and help achieve the overall goal of reducing the disproportionate safety incidents Latinos suffer in the construction industry.
Keywords: construction sectors; disproportionate incidents; Latinos; risk perception; safety; safety culture